Social studies learning modules to improve concept understanding and attitude of the environmental care - Ratna Wulan Sari; Pratiwi Pujiastuti (Journal of Education and Learning (EduLearn), 2023)
This study aimed to produce a suitable module to improve the understanding of environmental care concepts and attitudes of fourth-grade elementary school students and determine the module’s effectiveness. The data collection instruments consisted of a teacher interview guide, a student preliminary study questionnaire, a media expert validation questionnaire, material and instrument experts, a teacher response questionnaire, a student response questionnaire, and environmental care attitude assessment questionnaire, and a concept understanding ability test. The feasibility assessment uses assessments from media experts, learning material experts, and learning instruments. The practicality assessment of the module consists of a teacher response questionnaire and a student response questionnaire. The data analysis of the module’s effectiveness on the ability to understand the concept and attitude of caring for the environment was analyzed using the t-test and MANOVA test with a significance level of 0.05. The results of the study showed that: i) The module met the eligibility criteria based on the results of assessments from media experts, learning materials experts, and learning instruments that get an assessment in the “very feasible” category to use; ii) The module met the practicality criteria based on the results of the teacher response questionnaire assessment and the student response assessment questionnaire who received an assessment in the “very feasible” category; iii) The module was effective in increasing students’ understanding of concepts and environmental care attitudes. The effectiveness is shown from the t-test and MANOVA test results with a significance level of 0.001.